Assessment and analysis of multi-biomass fuels for sustainable electricity generation. (December 2021) - Wiranarongkorn, Kunlanan; Phajam, Picharporn; Im-orb, Karittha; Saebea, Dang; Arpornwichanop, Amornchai
Abstract: Many biomass power plants are not flexible, using only one fuel type, and have high CO2 emissions. In this study, a new methodology to assess the multi-biomass utilization for a power plant is proposed. The results provide that the proportions of mixed biomass residues in different regions of Thailand are appropriate with lower chloride content and slagging inclination than the standard specification. However, high alkali metal oxides in biomass in the southern region lead to high fouling inclination with high fly ash deposition. The electricity production using multi-biomass fuel is more efficient with lower fuel consumption than that with single-type biomass. To generate 103.43 MW electricity production, 107.89 t h −1 consumption of mixed biomass fuels in the central is lower than that with multi-biomass in other regions. However, it generates a maximum of 12.5 mol% CO2 in exhaust gases which can be captured by suitable amine-based absorbents with 90.82% efficiency. Highlights: Methodology to assess the multi-biomass utilization for a power plant is proposed. Circulating combustion of multi-biomass fuels for power production is investigated. A biomass power plant using multi-biomass fuels with CO2 capture is designed. 90.82% CO2 is captured after combustion, with low solvent and energy usage.